Analytical Applications of Options Trading - Ehsan, Muhammad Asif (International Journal For Research In Business, Management And Accounting, 2018)
An option is a contract that gives the holder the right, but not the obligation, to buy or sell an underlying asset at a predetermined price for a specified period of time. Options are the most versatile and unique financial instruments as they are available on a large variety of underlying assets like common stock, currencies, debt instruments, interest rates and so on. Options on stock indices and futures contracts, wherein the underlying asset is a futures contract, are also traded on organized options exchanges. The paper notes that the main disadvantage of over-thecounter market is that the option writer (seller) may default. It means that the buyer is subject to credit risk. In order to overcome this problem, market participants adopt a number of measures such as calling for some collateral from the counterparties. Although the market participants are free to trade in options using their own requirements, standard terms and conditions for OTC options and guidelines for trading practices are governed by International Currency Options Market (ICOM) or International Swap Dealers Association Incorporation (ISDA).